Effects of chronic oral monosodium glutamate consumption on naloxane-induced morphine withdrawal in infant rats - YANANLI, HASAN RACİ (My University, 2022)
Aim: The aim of this study was to investigate chronic oral monosodium glutamate (MSG) consumption effects on symptoms of withdrawal, locomotor activity, and anxiety in morphine withdrawal syndrome induced by naloxone in infant rats. Material and Methods: Twelve 21-day-old male Wistar rats used in the study. Infant rats were given unlimited access to saline (control group) or MSG (MSG group) added to drinking water for 32 days. Withdrawal was induced by naloxone in morphine-dependent rats. Evaluation of withdrawal symptoms and anxiety were performed simultaneously with locomotor activity measurements. Unpaired two-tailed t-test was used for statistical analysis. Results: Withdrawal sings, such as jumping, wet dog shake, and weight loss; stereotypic, ambulatory, and vertical locomotor activity movements; central, peripheral, and total activities used in the assessment of anxiety in infant rats with naloxone-induced withdrawal syndrome that consumed oral MSG for 32 days were not different from the control group. Conclusion: These findings obtained in our study indicate that chronic consumption of oral MSG in infant rats whose blood-brain barrier has not yet developed does not affect morphine dependence and naloxone-induced withdrawal. Further studies are needed to investigate the mechanism of action of orally administered MSG.

Amaç: Bu çalışmanın amacı yavru sıçanlarda ağızdan kronik monosodium glutamate (MSG) tüketiminin naloksonla tetiklenmiş morfin yoksunluk sendromunda yoksunluk bulguları, lokomotor aktivite ve kaygı üzerine etkilerinin araştırılmaktır. Gereç ve Yöntemler: Çalışmada on iki adet 21 günlük erkek Wistar sıçan kullanılmıştır. Yavru sıçanların içme suyuna ilave edilen salin (kontrol grubu) veya MSG’e (MSG grubu) 32 gün boyunca sınırsız erişimleri sağlandı. Morfin bağımlılığı geliştirilen hayvanlarda yoksunluk nalokson ile tetiklendi. Yoksunluk bulgularının ve kaygının değerlendirmesi lokomotor aktivite ölçümleri ile eşzamanlı yapıldı. İstatistiksel analizde unpaired two-tailed t-testi kullanıldı. Bulgular: 32 gün boyunca ağızdan MSG tüketen sıçanlarda naloksonla tetiklenen yoksunluk sendromunda zıplama, ıslak köpek silkinmesi ve kilo kaybı gibi yoksunluk bulguları; stereotipik, ambulatuvar ve vertikal lokomotor aktivite hareketleri ve kaygının değerlendirilmesinde kullanılan santral, periferik ve total aktiviteler kontrol grubundan farklı değildi. Sonuç: Çalışmamızda elde edilen bu bulgular MSG’ın kan-beyin bariyeri henüz gelişmeyen yavru sıçanlarda kronik oral tüketiminin morfin bağımlılığını ve naloksonla tetiklenen yoksunluğunu etkilemediğine işaret etmektedir. Ağızdan alınan MSG’ın etki mekanizmasının araştırması için daha ileri çalışmalara ihtiyaç vardır
Kronik monosodyum glutamat tüketiminin yavru sıçanlarda naloksonla tetiklenen morfin yoksunluğu üzerine etkileri
Keywords: Kaygı; Zıplama; Lokomotor aktivite; Kilo kaybı; Islak köpek silkinmesi; Anxiety; Jumping; Locomotor activity; Weight loss; Wet dog shake